Lean Mass Longitudinally Confounds Sedentary Time and Physical Activity With Blood Pressure Progression in 2513 Children - Andrew O. Agbaje (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Randomized controlled trials have reported no effect of moderate‐to‐vigorous physical activity (MVPA) on reducing blood pressure (BP) in youth, probably due to short trial durations. This study examined the longitudinal effect of sedentary time (ST), light PA (LPA) and MVPA on BP in 11‐year‐old children followed up for 13 years to determine the confounding and mediating role of body composition. Methods Data included 2513 children from the Avon Longitudinal Study of Parents and Children (ALSPAC), UK birth cohort who had data on at least one time‐point measure of accelerometer‐based movement behaviour across the follow‐up and complete BP measures at ages 11, 15 and 24 years. Body composition was assessed with dual‐energy x‐ray absorptiometry at all time points. Multivariate adjusted generalized linear mixed‐effect model and structural equation causal mediation model analyses were conducted. Results Among 2513 participants (61% female, mean [SD] age 11.72 [0.21] years), ST steadily increased from ~6 h/day in childhood (age 11 years) to ~9 h/day in young adulthood (age 24 years), whereas LPA and MVPA decreased, but BP had an inverted U‐shaped increase. In the longitudinal analysis, after full adjustment, a 1‐min cumulative ST from ages 11 to 24 years was positively associated with increased systolic BP (0.009 mmHg [95% CI 0.007–0.011]; p < 0.001) and diastolic BP. A 1‐min cumulative LPA was inversely associated with systolic BP (−0.007 mmHg [−0.009 to −0.004]; p < 0.001), but not diastolic BP. In isotemporal substitution analyses, longitudinal replacement of 10 min of ST with equal time in LPA during childhood, adolescence and young adulthood cumulatively decreased systolic BP by −2.63 mmHg [95% CI −3.17 to −2.08] (p < 0.0001) and diastolic BP by −1.93 mmHg [95% CI −2.36 to −1.50] (p < 0.0001). Replacing 10 min of ST with 10 min of MVPA had no statistically significant effect due to an absolute confounding effect of lean mass. The association of ST with systolic BP was fully mediated by increased lean mass (93% mediation). Increased total fat mass partially mediated (19%–27%) the inverse associations of cumulative MVPA with cumulative systolic and diastolic BP. Conclusions Theoretically replacing 10 min/day spent sedentary with 10 min/day of LPA during growth from childhood through young adulthood may lower systolic BP by −3 mmHg and diastolic BP by −2 mmHg. Lean mass seems more significant than fat mass in the relations of ST and PA with BP and should be accounted for in future intervention studies in the paediatric and young adult population.